Contractor Performance And Operational Capabilities In Long Segment Maintenance Of National Road Delivery Projects - Bulba, Alfa Taras (2019)
Performance-based Contract (PBC) was applied in Indonesia national road as new approchment to substitute traditional way as commonly used. There are issues affect to PBC because of overloading, side friction, swampy, emergency and disputes. By this reason, PBC was modified to Long Segment Maintenance Contract (LSMC). Local contractors is force to construct and maintain in the same time at the length of territorial segment by performance measurement. However, due to of cultural changes, contractors are not realizing and optimizing their performance.